2018
DOI: 10.5539/jel.v7n3p233
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships Among Writing Skills, Writing Anxiety and Metacognitive Awareness

Abstract: The purpose of this study was to investigate the relationships among students’ argumentative text writing skills, writing anxiety, and metacognitive awareness. The participants were composed of 375 8th graders in six middle schools in Sivas. Metacognitive Awareness Inventory (B Form) which was adapted in to Turkish by Karakelle & Saraç (2007) and Writing Anxiety Scale which was developed by Yaman (2010) were used to collect data. The argumentative texts that were gathered from the students were evaluated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 16 publications
0
37
0
3
Order By: Relevance
“…Stewart, Seifert and Rolheiser (2015) have concluded that using metacognitive strategies increases self-efficacy perceptions and decreases writing anxiety of university students. Balta (2018) has concluded that students with low writing anxiety are more successful at argumentative writing compared to their colleagues with moderate or high anxiety levels.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Stewart, Seifert and Rolheiser (2015) have concluded that using metacognitive strategies increases self-efficacy perceptions and decreases writing anxiety of university students. Balta (2018) has concluded that students with low writing anxiety are more successful at argumentative writing compared to their colleagues with moderate or high anxiety levels.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…During classes, a considerable number of students expressed they were never taught writing skills deductively, and thus lacked knowledge and awareness of explicit rules on writing structure. While in writing, it is necessary to be aware of own thinking processes in order to explore the best way, foresee the possible mistakes, and reach accurate results in thought production and problem-solving (Balta, 2018).…”
Section: Martínez • López-díaz • Pérez Using Process Writing In the Tmentioning
confidence: 99%
“…Besides, Amiri and Ghonsooly (2015)categorized English classroom anxiety was a significant influence on English examination scores than other anxiety levels. Balta(2018)also argued in their research that the anxiety in the English class affect the students' final score of English Related to some existing effects of anxiety, students' anxiety measurement is a useful and beneficial way to investigate the students' measurement anxiety. This can be a decent factor for this feature and its similar aspects and not even that problem but also learning can be accelerated and the expenses decreased.…”
Section: Introductionmentioning
confidence: 99%